Relation between vitamin D and impulse behaviours in patients with eating disorder: a pilot observational study. (5th May 2020) - Todisco, Patrizia; Meneguzzo, Paolo; Vogazianos, Paris; Garolla, Alice; Antoniades, Athos; Tozzi, Federica
Abstract: Objective: There is growing evidence that vitamin D levels have a role not only in bone health and energy metabolism, but also for supporting nervous system and brain functions, including impulsivity. Impulsive behaviours are considered characteristics of great relevance in patients with Eating Disorders (ED) both for the course of the illness and for the treatment. The aim of this study is to examine the relationship between impulsive behaviours and vitamin D in patients with ED. Method: 236 patients with a diagnosis of ED, consecutively recruited at an ED ward between 2014 and 2018, were enrolled. Patients were classified as impulsive or non‐impulsive based on the presence of clinically relevant impulsive behaviours. Results: Impulsive patients were found to have statistically significant lower levels of vitamin D than non‐impulsive ( p = .007). A threshold value of 20.4 ng/ml for discriminating impulsive from non‐impulsive patients was found. Discussion: This hypothesis generating study partially confirmed a relationship between vitamin D deficiency and impulsive behaviours in ED spectrum mediated by body weight, even if results were not confirmed after corrected by obesity. No definitive conclusion may be taken on whether the effect is reduced due to the loss of power. Future directions are discussed.